Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To express [tex]\((5 \sqrt{2} - \sqrt{5})(\sqrt{2} - \sqrt{5})\)[/tex] in the form [tex]\(a + b \sqrt{c}\)[/tex], we'll follow these steps:
1. Explicit Multiplication: First, distribute the terms using the distributive property (FOIL method).
[tex]\[ (5 \sqrt{2} - \sqrt{5})(\sqrt{2} - \sqrt{5}) = (5 \sqrt{2})(\sqrt{2}) + (5 \sqrt{2})(-\sqrt{5}) + (-\sqrt{5})(\sqrt{2}) + (-\sqrt{5})(-\sqrt{5}) \][/tex]
2. Simplify Each Product:
- [tex]\((5 \sqrt{2})(\sqrt{2})\)[/tex]: Multiplying the terms, we get [tex]\(5 \sqrt{2 \cdot 2} = 5 \sqrt{4} = 5 \cdot 2 = 10\)[/tex].
- [tex]\((5 \sqrt{2})(-\sqrt{5})\)[/tex]: Multiplying gives [tex]\(-5 \sqrt{2 \cdot 5} = -5 \sqrt{10}\)[/tex].
- [tex]\((-\sqrt{5})(\sqrt{2})\)[/tex]: Multiplying gives [tex]\(-\sqrt{5 \cdot 2} = -\sqrt{10}\)[/tex].
- [tex]\((-\sqrt{5})(-\sqrt{5})\)[/tex]: Multiplying gives [tex]\(\sqrt{5 \cdot 5} = \sqrt{25} = 5\)[/tex].
3. Combine Like Terms:
- From the first product, we get [tex]\(10\)[/tex].
- From the second and third products, we combine the terms with [tex]\(\sqrt{10}\)[/tex]:
[tex]\(-5 \sqrt{10} - \sqrt{10} = -6 \sqrt{10}\)[/tex].
- From the fourth product, we get [tex]\(5\)[/tex].
Putting it all together:
[tex]\[ 10 + 5 - 6 \sqrt{10} \][/tex]
4. Combine Constants:
- Combine the constant terms [tex]\(10 + 5\)[/tex]:
[tex]\[ 15 \][/tex]
So, finally combining all terms, we have:
[tex]\[ 15 - 6 \sqrt{10} \][/tex]
The expression [tex]\((5 \sqrt{2} - \sqrt{5})(\sqrt{2} - \sqrt{5})\)[/tex] in the form [tex]\(a + b \sqrt{c}\)[/tex] is:
[tex]\[ a = 15, \quad b = -6, \quad \text{and} \quad c = 10 \][/tex]
Thus, the final result is:
[tex]\[ 15 - 6 \sqrt{10} \][/tex]
In this problem, we have:
[tex]\[ a = 0, \quad b = 8, \quad c = 2 \][/tex]
1. Explicit Multiplication: First, distribute the terms using the distributive property (FOIL method).
[tex]\[ (5 \sqrt{2} - \sqrt{5})(\sqrt{2} - \sqrt{5}) = (5 \sqrt{2})(\sqrt{2}) + (5 \sqrt{2})(-\sqrt{5}) + (-\sqrt{5})(\sqrt{2}) + (-\sqrt{5})(-\sqrt{5}) \][/tex]
2. Simplify Each Product:
- [tex]\((5 \sqrt{2})(\sqrt{2})\)[/tex]: Multiplying the terms, we get [tex]\(5 \sqrt{2 \cdot 2} = 5 \sqrt{4} = 5 \cdot 2 = 10\)[/tex].
- [tex]\((5 \sqrt{2})(-\sqrt{5})\)[/tex]: Multiplying gives [tex]\(-5 \sqrt{2 \cdot 5} = -5 \sqrt{10}\)[/tex].
- [tex]\((-\sqrt{5})(\sqrt{2})\)[/tex]: Multiplying gives [tex]\(-\sqrt{5 \cdot 2} = -\sqrt{10}\)[/tex].
- [tex]\((-\sqrt{5})(-\sqrt{5})\)[/tex]: Multiplying gives [tex]\(\sqrt{5 \cdot 5} = \sqrt{25} = 5\)[/tex].
3. Combine Like Terms:
- From the first product, we get [tex]\(10\)[/tex].
- From the second and third products, we combine the terms with [tex]\(\sqrt{10}\)[/tex]:
[tex]\(-5 \sqrt{10} - \sqrt{10} = -6 \sqrt{10}\)[/tex].
- From the fourth product, we get [tex]\(5\)[/tex].
Putting it all together:
[tex]\[ 10 + 5 - 6 \sqrt{10} \][/tex]
4. Combine Constants:
- Combine the constant terms [tex]\(10 + 5\)[/tex]:
[tex]\[ 15 \][/tex]
So, finally combining all terms, we have:
[tex]\[ 15 - 6 \sqrt{10} \][/tex]
The expression [tex]\((5 \sqrt{2} - \sqrt{5})(\sqrt{2} - \sqrt{5})\)[/tex] in the form [tex]\(a + b \sqrt{c}\)[/tex] is:
[tex]\[ a = 15, \quad b = -6, \quad \text{and} \quad c = 10 \][/tex]
Thus, the final result is:
[tex]\[ 15 - 6 \sqrt{10} \][/tex]
In this problem, we have:
[tex]\[ a = 0, \quad b = 8, \quad c = 2 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.